Spatial distribution and risks factors of porcine cysticercosis in southern Benin based meat inspection records - GOUSSANOU ., J.S.E; KPODEKON, TCHOKPONHOUE TCHEGNINOUGBO MARC; SAEGERMAN, CLAUDE; AZAGOUN, E.; YOUSSAO ABDOU KARIM, ISSAKA; FAROUGOU, SOUAÏBOU; PRAET, N; GABRIËL, S; DORNY, P.; KORSAK, N (My University, 2013)
Porcine cysticercosis, which is widely distributed in Africa, causes financial losses and diseases among humans. To control the disease in an area, it is important to know the geographical distribution. In this study, spatial distribution of porcine cysticercosis in southern Benin was performed. By using the number of partial organ seizures at meat inspection, the study has revealed high risks of porcine cysticercosis in administrative districts of Aplahoue, Dogbo, Klouekanme and Lokossa. The proportion of seizures ranged from 0.06% for neck muscles to 0.69% for tongues. Spatial analysis of carcass seizure frequencies revealed Akpro Misserete, Avrankou, Dangbo, Porto-Novo, Ifangni and Aguegues as the most likely clusters (P<0.001) for porcine cysticercosis distribution. The risk factor found to be associated with the porcine distribution was the Taenia solium cysticerci positive testing using lingual examination by butchers and retailers. Catching of pig within the Zou and Mono department and pigs directly purchased by the butcher were found protective factors for distribution of porcine cysticercosis in southern Benin.
Keywords: Cysticercosis; spatial distribution; satscan; risk factor; southern Benin